2023
DOI: 10.4102/sajpsychiatry.v29i0.1869
|View full text |Cite
|
Sign up to set email alerts
|

Trauma survivors’ perceptions and experiences of prolonged exposure for PTSD at a psychology clinic

Abstract: Background: Several trauma-focused treatments have been developed to treat post-traumatic stress disorder (PTSD). Yet there are limited studies on how trauma survivors perceive and experience trauma-focused treatments such as prolonged exposure therapy (PE) for PTSD, especially in low- and middle-income countries (LMIC).Aim: The study aimed to explore the perceptions and experiences of trauma survivors receiving prolonged exposure therapy for PTSD and the general acceptability of PE for PTSD in a LMIC.Setting:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Once in treatment, some patients reported intentional behaviors aimed at making the most out of their treatment, cultivating a willingness to face fears associated with reliving their index-trauma. 50–52 , 81 , 82 , 84 , 85 , 89–95 In contrast, in the context of possessing a willingness to confront pain, some participants reported feeling incapable of engaging fully in imaginal exposure to traumatic events. This may be due to use of defenses, such as avoidance, and hesitancy about engaging in treatment due to psychosocial instability.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Once in treatment, some patients reported intentional behaviors aimed at making the most out of their treatment, cultivating a willingness to face fears associated with reliving their index-trauma. 50–52 , 81 , 82 , 84 , 85 , 89–95 In contrast, in the context of possessing a willingness to confront pain, some participants reported feeling incapable of engaging fully in imaginal exposure to traumatic events. This may be due to use of defenses, such as avoidance, and hesitancy about engaging in treatment due to psychosocial instability.…”
Section: Resultsmentioning
confidence: 99%
“…Studies highlighted the contribution of intrapersonal factors (eg, patient traits, beliefs, and internal resources) to the overall experience of treatment. [50][51][52]81,82,84,85,[89][90][91][92][93][94][95] Most studies referred to the significant psychological burden PTSD treatment entails (eg, fear of re-traumatisation, worsening of symptoms and functional destabilization). Correspondingly, in this synthesis, we found that intrapersonal factors reportedly influenced patients' perception of their experience of treatment, and conversely, their willingness to engage in often-challenging therapeutic processes.…”
Section: Readinessmentioning
confidence: 99%
See 3 more Smart Citations